Microvascular dysfunction during cardiac preservation. - Manciet, Lorraine Hanna. (The University of Arizona., 1989)
Heart transplantation is, for certain types of cardiovascular disease, the only form of treatment resulting in patient survival. Its clinical application is, however, limited by the shortage of donor organs. This shortage is largely due to the inability to consistently preserve adequate myocardial function over prolonged ischemic periods. It is the goal of this research to provide information which may contribute to techniques for heart preservation, thus improving graft survival following preservation and transplantation. Current methods for myocardial preservation generally involve the arrest and immersion of the heart in cold cardioplegic solution, the composition of which is designed to provide for the reduced metabolic demands of the cold, arrested muscle. These methods have extended the preservation period to approximately 6 hours; however, hearts cannot be held longer than this period because, although metabolism has been slowed by hypothermia, alterations take place which compromise functional recovery upon reperfusion. A variety of perfusates and perfusion techniques have been developed to protect the myocardium from the damage thought to occur as a consequence of ischemic storage of the isolated heart. However, a consistently successful technique for long-term preservation of the heart remains undefined. A growing body of knowledge has led to the hypothesis that injury to the microcirculation may result in myocardial ischemia during preservation and decreased contractile function following preservation. To test this hypothesis, standard Langendorff techniques for the measurement of left ventricular function were combined with biochemical, histological and morphological techniques to determine: (1) whether loss of microvascular function occurs in isolated hearts hypothermically perfused with an oxygenated solution; (2) the impact of microvascular dysfunction during the preservation period on the functional recovery of hearts; and (3) which mechanisms contribute to decreased microvascular function during preservation. This experimental approach will allow for characterization of the role of the microvasculature in decreased contractility of preserved hearts and will provide information regarding the contribution of specific mechanisms to the compromised contractility of preserved hearts. Systematic evaluation of mechanisms thought to be responsible for decreased contractility of isolated hearts could contribute to improved myocardial preservation techniques that can be applied to clinical transplantation.